The Pedagogical Museum of Otones. A rural experience in the diffusion of the educational heritage - Juan Francisco CEREZO MANRIQUE; Miguel Ángel CEREZO MANRIQUE (Ediciones Universidad de Salamanca, 2017)
The project of the Otones Educational Museum must be placed in the framework of the creativity of the late twentieth century which appear throughout Spain in order to recover and spread educational heritage. This proposal, created and developed in a series of activities by the Asociation town of El Corralón and its Cultural Association, which have been promoting Education since the beginning of the democratic era, is intended as a modest contribution, particularly in its rural dimension. It also is a collective task that provides opportunities for participation and cultural creation for any essential rural development project. During its 20 years of history (1996-2016) it has been regarded as a place for citizens for meeting and dialogue, where recovered information and restoration of educational memory facilitate processes for improving the quality of life. Moreover, the Otones Museums, and particularly the Educational museum, have become a key dynamic element of culture and education in this small town.